Pengembangan Aplikasi Android Rekomendasi Tempat Wisata Belanja di Kota Malang dengan Group Decision Support System (GDSS) dan Location-Based Service (LBS) - Felinda Gracia Lubis; Ratih Kartika Dewi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Malang has so many tourist attractions that could be visited each day, starting from nature tourism, education tourism, arts and culture, and many more. One of the tourist attractions that is interesting to be visited by the tourists is its shopping tourism. Malang has variety of shopping places that makes it so difficult for the tourists to choose one. It is proven by 43 respondents are claiming that each member of the group has their own preferences to choose a shopping place. This shopping recommendation system was developed on Android-based mobile devices because it has enough features, viz. Global Positioning System (GPS) and Google Maps. The algorithm used to get the group recommendation is TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method, which is used to get alternative ranking based on user's preferences and BORDA to get group voting. This system is tested with 3 different testings, viz. Black Box testing, algorithm validity testing and usability testing. The results of Black Box testing shows that the functionality of the system is 100% valid. The algorithm validity testing was done by comparing the results from the system and the manual calcultaion. The results of this testing shows that the algorithm used in the system is valid. The last testing for the system is the usability testing. It was done to know the user's perception of the system. The final result of this testing shows that the system is acceptable with the total average 77, grade C and categorized as good..